Public policy implementation barriers on field level bureaucrats of the national agency for food and drug administration and control in Nigeria - Ogirima, Isyak Ibrahim; Feliciab, Uloko (2020)
The aim of this paper is to analyze the activities of field level bureaucrats to describe how they act to overcome barriers that affect policy implementation. While most polices rely on field level bureaucrats for their implementation, there is still a lack of empirical studies that provide an adequate understanding of how field bureaucrats can overcome the barriers, delays, and disincentives associated with implementing policies. For this reason the author decided to examine how field level bureaucrats are influenced by barriers and how the influences from the barriers affects their work – policy implementation. The research was conducted using a case study model, as such two policies – processed food regulatory policy and herbal medicine and related product advertisement regulatory policy of the National Agency for Food and Drug Administration and Control was studied. Both primary and secondary data were sourced for the research.. The researcher recommends that attention should be given to the behavior of field bureaucrats on duties, in such a way as to ensure that the behavior they depict are those that will not compromise the policy in their care, so as to ensure more positive outcomes.